Immediate supervisor’s satisfaction on teaching competence of teachers product by one state college in Western Visayas Philippines - Soceline N. Batisla-ong (International Research Journal of Science, Technology, Education, and Management, 2022)
Higher Education Institutions (HEIs) in the Philippines are focusing on graduates employability. The immediate supervisors’ demand is very high as they look for graduates who are flexible, willingness to learn the job, technically competent, and committed to excellence. Thus, this study was conducted to determine immediate supervisors’ satisfaction on teaching competence of teachers produced by one State College in Western Visayas. The descriptive-quantitative research design with a standardized research instruments was employed. Since there were a total of 48 graduates in the year 2002-2019 the researcher decided to take them all as respondents. Frequency count, percentage, and mean were used in the descriptive statistical test and Mann-Whitney and Kruskall Wallis analysis for differences in the immediate supervisors’ satisfaction and teachers teaching competence level. Results revealed that respondents’ instructional skills, personal and social qualities were rated as “Surpasses Expectations” and “Very Satisfactory” in teaching competence. Moreover, it was found out there is no significant difference in the immediate supervisors’ satisfaction and on the teaching competence of teachers as to program, position, and number of years in teaching. Notably, results exclaimed that one of the college in Western Visayas is producing graduates who are viable to the academic institution where they teach. Furthermore, the school should not remain complacent considering the fast-changing advancement in the educational arena. Thus, the school administration and the dean of the college of education should closely monitor and evaluate the effectiveness of the varied teaching strategies used by teachers ensuring that it enhance students’ communication, creativeness, and critical thinking skills.